2018
DOI: 10.12659/msm.911231
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Reduces the Incidence of Postoperative Nausea and Vomiting in Children Undergoing Endoscopic Adenoidectomy under General Anesthesia Without Increasing the Risk of Postoperative Hemorrhage

Abstract: BackgroundPostoperative nausea and vomiting (PONV) is a common complication of pediatric anesthesia, but the overall incidence of PONV in patients undergoing adenoidectomy is unknown. The aim of this controlled study was to compare the effect of dexamethasone administration with placebo to reduce PONV in children undergoing endoscopic adenoidectomy under general anesthesia.Material/MethodsA randomized placebo-controlled study included 118 pediatric patients who underwent elective endoscopic adenoidectomy under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…All patients underwent intraoperative and 5-day post-surgical antibiotic prophylaxis with oral amoxicillin and clavulanic acid (70 mg amoxicillin/10 mg clavulanate/kg in three daily doses) or oral clarithromycin (15 mg/kg in two daily doses, in patients with known beta-lactam or clavulanate allergies). Furthermore, intraoperative steroid prophylaxis with dexamethasone 0.15 mg/kg was given in all children to reduce postoperative nausea and vomiting 16 .…”
Section: Surgical Technique and Patient Managementmentioning
confidence: 99%
“…All patients underwent intraoperative and 5-day post-surgical antibiotic prophylaxis with oral amoxicillin and clavulanic acid (70 mg amoxicillin/10 mg clavulanate/kg in three daily doses) or oral clarithromycin (15 mg/kg in two daily doses, in patients with known beta-lactam or clavulanate allergies). Furthermore, intraoperative steroid prophylaxis with dexamethasone 0.15 mg/kg was given in all children to reduce postoperative nausea and vomiting 16 .…”
Section: Surgical Technique and Patient Managementmentioning
confidence: 99%
“…Earlier lots of studies have shown that postoperative nausea and vomiting(PONV) is one of the most common adverse events after laparoscopic surgery with a reported incidence of 40-75%, which may delay postoperative recovery and discharge [2,3]. In addition, PONV is the leading cause of discontinuation of intravenous patient-controlled analgesia (PCA), leading to decrease in the patient satisfaction and increase in the adverse effects (including the postoperative catheter-related bladder discomfort) [3,4]. So, PONV in patients scheduled for laparoscopic surgery has been prevented and treated with a variety of antiemetics [4].…”
Section: To the Editormentioning
confidence: 99%
“…Six studies [8,10,13,15,17,19] reported the incidence of POV in the dexamethasone and placebo groups. In the Madan study [13], dexamethasone was compared at three different doses (0.25, 0.5, 1.0 mg/kg), and we selected all groups as dexamethasone groups for meta-analysis because dexamethasone in other studies was administered at doses ranging from 0.15 mg/kg to 1.0 mg/kg.…”
Section: Dexamethasone Intravenous Injection and Rescue Antiemeticmentioning
confidence: 99%
“…Four studies [8,10,15,19] reported the incidence of PON between the dexamethasone and placebo groups. The results showed that the incidence of PON in the dexamethasone group was significantly lower than that in the placebo group (RR 0.40, 95% CI 0.27-0.59, P<0.01; NNT =4.40; n =415; Figure 3).…”
Section: Dexamethasone Intravenous Injection and Rescue Antiemeticmentioning
confidence: 99%
See 1 more Smart Citation